An approach to fish-hook injury in children in remote hospital: A case report and brief literature review - Manyangbo, Suryaman; Devkota, Harihar (Journal of Chitwan Medical College, 2017)
Background: Fish-hook injury is a leisure activity based for many across the globe among adults. Sometimes, it has been occasionally happened in the playing group children when the fishing rod with hook kept carelessly and children try to play and caught hand or bodily injury. If the hook is snug then it becomes difficult to removal. We report two cases of such injury in the hand and discuss the technique for its removal with a short literature review. Cases: A 3 year and 15 years old male accidently suffered a fishhook into their great thumb. They came to the surgical OPD one day and same day respectively after the incident with pain. Unsuccessful attempts at removal were made. A retrograde pull method was applied to remove fish hooks successfully. Conclusion: Fish-hooks can be removed in children less traumatically following same technique for adult with a proper wound and pain care.